Perception of the Economic Impact of the COVID-19 Pandemic on Tabasco's Microenterprises and the Role of the Internet in its Preservation - López Moreno, Cristina del Carmen; García Rodríguez, José Félix (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2023)
OBJECTIVE: To analyze and identify the economic impact of the pandemic on MSMEs in Tabasco, as well as to describe the role played by the Internet in the preservation of these enterprises.MATERIAL AND METHOD: The research design is descriptive, documentary and exploratory with a quantitative approach. The study population is composed of 70 microenterprises in Villahermosa, Tabasco. A questionnaire adapted from the instrument applied by INEGI on the economic impact generated by COVID-19 on the companies was used to collect information.RESULTS: The decrease in income of the MSMEs was the main problem, as it led to the partial or definitive closure of the enterprise, since these were no longer sufficient to keep them operating. As a response, they opted to carry out home office and try to adapt to the new reality.CONCLUSIONS: The micro-enterprises interviewed suffered economic effects during the pandemic, such as: reduction of personnel, increase in delays in the payment of their debts by their clients and buyers, decrease in demand, cancellation of their orders, and decrease in their income. The use of the Internet was a fundamental strategy for its permanence.
Keywords: COVID-19; MSMEs; Internet; Information tecnnology.